KEBERLANJUTAN DAN NILAI PERUSAHAAN: ANALISIS PRAKTIK GREEN INNOVATION PADA PERUSAHAAN - Ulwiyah, Badi’atul; Mahirun, Mahirun (Transpublika Publisher, 2024)
This research examines how environmental performance, environmental efficiency and green innovation affect business value, amidst increasing demands for green practices. While companies are encouraged to meet regulations and market expectations, the impact of green practices on business value is not fully understood, especially in Indonesia. Companies in the LQ45 index are the focus of this study, uses Price to Book Value (PBV) and Return on Assets (ROA) as moderating variables. This study uses the Partial Least Squares (SEM-PLS) analysis approach. The findings show that leverage and green innovation have a strong beneficial impact on corporate value, while environmental efficiency has no significant effect and environmental performance has a negative effect. ROA does not act as a moderator between these factors. Although green innovation and leverage can increase corporate value, achieving environmental performance requires a more mature approach. The impact of these factors on firm value is not controlled by profitability as measured by ROA.